Role Of Caffeine As A Bowel Stimulant After Major Gynecological Surgeries - Maria Jabeen; Tahira Yasmeen; Lubna Riaz; Naila Parveen; Amina Raza; Fareeha Butt (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: To investigate the role of caffeine as a bowel stimulant after major gynecological surger- ies. Coffee is a low-cost strategy to accelerate postoperative recovery of intestinal function/motility af- ter colorectal and gynecological surgery. Postoperative ileus or bowel paralysis is quite common in the postoperative period after abdominal surgery, such as elective colectomy, colorectal resection, caesarean section, or gynecological surgery. The occurrence of postoperative ileus leads to pro- longed patient hospital stay. Methods: This randomized control study was single-centered, conducted in Obstetrics and Gynecol- ogy department of Liaquat National Hospital Karachi after approval from Research and Ethical review committee of hospital (Ref#:0416-2019-LNH-ERC ). The duration of study was one year from 20th February2019 to 20th February 2020. In this randomized controlled trial, 120 patients were randomly assigned before major gynecological surgery into control and intervention groups. Results: A total of 120 women who met the inclusion and exclusion criteria were included in the study. Descriptive statistics of the demographic data were similar between the two groups. Statistical significant difference (p= 0.001) was found between the mean time (23±6.9 vs. 30±9.4 hours) for the passage of first flatus between the intervention group and the control group. Mean time to first bowel movement (37±6.8 vs. 30±4.8 hours), mean time to first defecation (42±8.3 vs.32±6.6 hours) and mean length of hospital stay after surgery (101±7.8 vs.72±5.6 hours) showed statistical significant difference between the two groups with p-value<0.05. Conclusion: Coffee consumption (caffeine) after major gynecological surgery played an important role as a bowel stimulant. Drinking coffee reduced the mean time for first passage of flatus, First bowel sound, first defecation, and hours of hospital stay after surgery.